A Big Year for Open Access Chemistry Publishing. Issue 1 (8th January 2020) - Novara, Francesca Rita
Abstract : Starting 2020 with an open mind ! The new Editor‐in‐Chief of ChemistryOpen Francesca Novara looks back on her first year with the journal and discusses the increasingly strong position of ChemistryOpen in a developing open access world.